Effects of spaceflight on cancellous and cortical bone in proximal femur in growing rats() - Gamboa, Amanda (Bone Rep, 2021)
Mechanical loading of the skeleton during normal weight bearing plays an important role in bone accrual and turnover balance. We recently evaluated bone microarchitecture in the femoral head in 5.6-week-old male Sprague Dawley rats subjected to a 4-day spaceflight aboard STS-41. Compared to weight bearing ground controls, cancellous bone volume fraction was dramatically lower in animals subjected to microgravity. The effects of spaceflight on the rat skeleton are potentially influenced by factors such as age, duration of flight, strain and sex. To test the generalizability of our initial observation, we evaluated archived proximal femora from two additional spaceflight missions: a 10-day mission (STS-57) with 7.5-week-old male Fisher 344 rats, and a 14-day mission (STS-62) with 12-week-old ovariectomized (ovx) female Fisher 344 rats. Cancellous microarchitecture and cortical thickness were assessed using x-ray microtomography/microcomputed tomography. In male rats, cancellous bone volume fraction (bone volume/tissue volume) was lower in flight animals compared to flight controls, but differences were not significant compared to baseline. In ovx female rats, cancellous bone volume fraction was lower in flight animals compared to flight controls and baseline, indicating net bone loss. Cortical thickness did not differ among groups in either experiment. In summary, findings from three separate studies support the conclusion that spaceflight results in cancellous osteopenia in femoral head of growing rats.